Energy balance during an Ironman triathlon in male and female triathletes - Kimber, N. E.; Ross, J. J.; Mason, S. L.; Speedy, D. B. (International Journal of Sport Nutrition and Exercise Metabolism, 2002)
Energy balance of 10 male and 8 female triathletes participating in an Ironman event (3.8-km swim, 180-km cycle, 42.2-km run) was investigated. Energy intake (EI) was monitored at 7 designated points by dietary recall of food and fluid consumption. Energy expenditure (EE) during cycling and running was calculated using heart rate-VO2 regression equations and during swimming by the multiple regression equation: Y = 3.65v + 0.02W - 2.545 where Y is VO2 in L * min-1, v is the velocity in m * s-1, W is the body weight in kilograms. Total EE (10,036 ± 931 and 8570 ± 1014 kcal) was significantly greater than total EI (3940 ± 868 and 3115 ± 914 kcal, p < .001) for males and females, respectively, although energy balance was not different between genders. Finishing time was inversely related to carbohydrate (CHO) intake (g * kg-1 * h-1) during the marathon run for males (r = -.75, p < .05), and not females, suggesting that increasing CHO ingestion during the run may have been a useful strategy for improving Ironman performance in male triathletes.